Frictionally damped tool holder for long projection cutting tools - Denkena, Berend; Bergmann, Benjamin; Teige, Christian (Production engineering (Berlin, Germany), 2018)
The machining of complex geometries and deep cavities requires the use of long projecting tool holders. However, due to their high length-to-diameter ratio, these tool holders have a high degree of static and dynamic compliance. High dynamic compliance reduces process stability and thus productivity. A new approach to lessen this is to increase the damping of long projecting tool holders by using friction dampers integrated into the tool holder shaft. The mathematical description and experimental testing of large friction-damped tool holders are the subject of this paper. With the aid of experimental modal analysis and cutting tests, the dynamic compliance and maximal cutting depth were determined. Due to the integration of friction segments in the tool holder shaft, the maximal depth of cut could be increased about 75% compared to a reference tool holder with the same diameter and length configuration.